Development of Experimental Setup for Determining the Parameters of DC Motors Used in Mobile Robots - Gurgoze, Gurkan; Turkoglu, Ibrahim (Gazi Univ, 2022)
In studies about mobile robots, applications emerge on the basis of physical and simulation. Cost, material supply and loss of time of physical studies have increased the tendency to make applications in a simulation environment. The important point in simulation studies is the creation of a mathematical model that can represent the behavior of the real system. The mathematical model is built on DC motors. In this case, DC motor parameters should be known most accurately for the mathematical model. The lack or limitation of the parameters required in the data sheets of DC motors caused the parameters to be obtained by experimental measurements. Mechanisms set up for experimental measurements are usually in the laboratory environment and are complex, difficult to obtain materials and costly.Simpler experimental setups can be established with development cards and sensors developed in recent years. In this study, a simple experimental setup was created by with development card and sensors. PWM signal, speed, angular velocity of the motor was obtained through this experimental setup, and motor currents and voltages were measured with multimeter or measurement sensors. Parameters such as torque constant, opposing EMF, friction, armature resistance were obtained by methods such as curve fitting, Newton-Kirchhoff according to measurement values taken at certain intervals. Found parameters were tested in Matlab\Simulink environment.
Keywords: DC motors; mathematical model; motor parameter; transfer function